2019
DOI: 10.1590/1983-40632019v4954520
|View full text |Cite
|
Sign up to set email alerts
|

Seed physiological quality and harvest point of dovyalis fruits

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Heterogeneity of seed maturity between and within bunches is considered as important factors for germination potential (Kallow et al 2021). The level of fruit ripeness is related to physiological quality of seeds (Kaiser et al 2016;Villa et al 2019). The results of this study showed that with the advance of the ripening process, seeds extracted from fully-ripe fruits (yellow peel) generated seedlings with higher percentage and faster germination, also more vigorous in growth variables.…”
Section: Seed Germination Of M Acuminata Var Flavamentioning
confidence: 76%
See 1 more Smart Citation
“…Heterogeneity of seed maturity between and within bunches is considered as important factors for germination potential (Kallow et al 2021). The level of fruit ripeness is related to physiological quality of seeds (Kaiser et al 2016;Villa et al 2019). The results of this study showed that with the advance of the ripening process, seeds extracted from fully-ripe fruits (yellow peel) generated seedlings with higher percentage and faster germination, also more vigorous in growth variables.…”
Section: Seed Germination Of M Acuminata Var Flavamentioning
confidence: 76%
“…When the seeds were not completely mature, they could germinate, but did not result in seedlings as vigorous as those harvested at the appropriate ripening time. It was also observed from the lower amount of reserves deposited (endosperms) which may cause a limiting factor for the development of seedlings (Moiwend et al 2015;Villa et al 2019). The level of fruit maturity was also reported to affect in vitro seed germination percentage of M. ornata (Dayarani et al 2014).…”
Section: Seed Germination Of M Acuminata Var Flavamentioning
confidence: 99%
“…Similar fruit characteristics evaluation of Elaeagnus latifolia L was done by Rymbai et al (2020). Dovyalis fruit color varies during ripening from green to intense brown color and fruits reach their maximum size and biomass accumulation point when the exocarp color is brown while seed removal for propagation should be done when fruits are yellowish-green in hue (Villa et al, 2019). The highest final germination percentage (53%) was recorded in seed clipping treatment (T 6 ) which is in significant with fine sand rubbing treatment (T 1 ) (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Isso sugere a coloração como uma característica importante a ser analisada em estudos sobre a maturação de sementes, comportamento similarmente verificado com frequência nas colheitas de sementes em fase de completa maturação de Joannesia princeps. Para fins propagativos de Dovyalis hebecarpa, foi observado que a retirada das sementes deve ser feita em frutos colhidos a partir do estádio 2 (2.5GY 5/8), com coloração verde-amarelada, embora maior tamanho e acúmulo de biomassa tenham sido atingidos com coloração do exocarpo marrom pela carta de Munsell por 2.5YR 3/4no, no estádio 4 de maturação (VILLA et al, 2019).…”
Section: Caracterização Morfológica E Biometria Dos Frutos E Sementesunclassified